Agile Governance Dalam Pelayanan Publik Pada Pelabuhan Penyeberangan Ferry Air Putih Kabupaten Bengkalis - M. Azka Pradipta; Khotami (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study aims to find out how to implement agile governance in public services at the Ferry Crossing Port of Air Putih Bengkalis Regency, as well as its various challenges. This analysis is based on theory of agile governance according to Alexandre J. H. de o. Luna, Philippe Krutchen, and Hermano P. de Moura (2015), which includes six indicators, including: Good Enough Governance, Business Driven, Human Focused, Based On Quick Wins, Systematic and Adaptive Approach, Simple Design and Continuous Refinement. The approach used is qualitative descriptive, with data collection techniques through observation, in depth interview, and documentation. The results of the study show that the application of agile governance principles in public services at the Air Putih Port by the Transportation Department has seen various efforts made to create improvements in public services. However, there are still several obstacles in the field such as a lack of awareness from the public to order queuing, frequent damage to ships that have an impact on the accumulation of passengers, lack of attention to facilities at the port for maintenance.